The antibacterial activity of zinc oxide nanoparticle-loaded soft contact lens - Chew, Jactty *; Tong, Tommy *; Chua, Mun Lok *; Mohammad Ridwane, Mungroo *; Yap, Yi Xing; Misni Misran,; Gew, Lai Ti * (Bentham Science, 2022)
Introduction: Contact lenses coated with antibacterial agents may reduce the risk of microbial keratitis; however, to the best of our knowledge, such contact lenses are not available on the market. Methods: We determined the ability of zinc oxide nanoparticles (ZnO-NPs)-loaded soft contact lenses to prevent the adhesion of Staphylococcus aureus and Pseudomonas aeruginosa. Commercially acquired sterile silicone hydrogel contact lenses were soaked in ZnO-NPs (˂50 nm) suspensions of various concentrations, and the stability of the ZnO-NPs coating on contact lenses over 28 days was monitored using a UV-vis spectrophotometer. The cytotoxicity effects of ZnO-NPs on human corneal epithelial cells were evaluated using a lactate dehydrogenase (LDH) kit. Results and Discussion: The results showed that the ZnO-NPs coating on contact lenses was optimal from day seven onward. In the following assays, optimally, ZnO-NP-coated contact lenses were incubated with S. aureus and P. aeruginosa suspensions (1 x 105 colony forming unit) for 24 hr at 37°C, followed by enumeration using the plating method. Our data showed that 100 ppm of ZnO-NPs coating on contact lenses reduced the adhesion of 69.9% and 74.6% of S. aureus and P. aeruginosa significantly (p<0.05). The confocal laser scanning microscopic analyses were consistent with our bacterial adhesion findings. Low cytotoxicity against human corneal epithelial cells was observed even at the highest concentration of 300 ppm. Conclusion: This study provides insights into the potential role of ZnO-NPs in developing contact lenses with antibacterial properties.